O pictórico na poesia cabo-verdiana: dos Claridosos a Kiki Lima - Oliveira Júnior, José Leite de (2009)
The relationship between literature and painting has been urging philosophers from Greek and Latin ancient cultures. Currently new branches in Semiotiks are being developed for this purpose. This research is based on semiotic theory of Jean-Marie Floch or, more precisely, on the adaptation of this theory to the Brazilian culture made by Antonio Vicente Pietroforte. Fora research subject was chosen painting and poetry of Cape Verde, aiming to clarify the following question: The paintings by Kiki Lima relates to the historical journal Claridade?Claridade were in all only nine editions (1936 to 1960). However, around the magazinewriters called "Claridosos" discussed the cultural typology of Cape Verde and has influenced the decision for independence of that country. Despite the dictatorship, the claridosospublished trials of high-level ficcional texts and poems, whose content has become a full of meaning heritage for the people of Cape Verde. Through the cultural mirror of Brazil, theclaridosos built a thesis on the creolization in Cape Verde. According to Manuel Ferreira, themain editions of the journal Clarity was drought and famine, migration and insularity. Theresistance to the tendency to emigrate as a solution to personal and national problems wererecurring in the work of claridosos. Kiki Lima (1953), the most important painter of CapeVerde, establishes a connection between his painting and the literature journal Claridade. In the mature phase of his work, radically changed his strategy to show the Cape Verdean people. Instead of showing a miserable scene of his country, he decided to present positive images of the every day life in Cape Verde. That decision has influenced you the technique ofpainting. In the mature phase, two main colors show up on the screen: the blue-cyan andorange. These colors, complementary colors in the palette, are absolutely contraries one to theother. In a semiotic approach, the roles of cyan and orange represents the manifestation of amore abstract dichotomy. In a individual level, the dichotomy of the generative sense of meaning is the life and death; in the society relationship, the dichotomic words are nature and culture. Orange refers to the body (individual) and the land (society); cyan refers to theclothing (individual) and the sea (society). Kiki Lima favors the role of the orange while hedevalues the cyan. Denying the cyan, he denies the sea and the clothing or, by analogy,respectively he denies the migration and foreign culture. Valuing the orange paint, heidentifies with the body and the land. And here is the solution to the tendency to migrate. Thisstrategy responds positively to the semiotics proposed by the poetic of the group claridosos.In conclusion, Kiki Lima intuitively transfer from the pages of poetry of the generation of Claridade to the screen of contemporary art's most important cultural problem of Cape Verde, namely, the tendency to emigrate. However, he proposes to solve it not by negative images of the Cape Verdean population, but by a happy contrast between the cyan and orange. In this battle of colors, the orange wins. The positive sanction of the warm color symbolizes the victory of the Creole culture.